Phosphate binding in the active centre of tomato multifunctional nuclease TBN1 and analysis of superhelix formation by the enzyme - Stránský, Jan; Koval', Tomáš; Podzimek, Tomáš; Týcová, Anna; Lipovová, Petra; Matoušek, Jaroslav; Kolenko, Petr; Fejfarová, Karla; Dušková, Jarmila; Skálová, Tereza; Hašek, Jindřich; Dohnálek, Jan (Acta crystallographica. Section F, Structural biology communications, 2015)
Tomato multifunctional nuclease TBN1 belongs to the type I nuclease family, which plays an important role in apoptotic processes and cell senescence in plants. The newly solved structure of the N211D mutant is reported. Although the main crystal-packing motif (the formation of superhelices) is conserved, the details differ among the known structures. A phosphate ion was localized in the active site of the enzyme. The binding of the surface loop to the active centre is stabilized by the phosphate ion, which correlates with the observed aggregation of TBN1 in phosphate buffer. The conserved binding of the surface loop to the active centre suggests biological relevance of the contact in a regulatory function or in the formation of oligomers.
Keywords: superhelix; krystalizace; vazebná místa; sekvence aminokyselin; Plant Proteins; endodeoxyribonukleasy; Molecular Sequence Data; type I nuclease; TBN1; Amino Acid Sequence; rostlinné proteiny; Endodeoxyribonucleases; Phosphates; tomato multifunctional nuclease; molekulární sekvence - údaje; multienzymové komplexy; Protein Structure, Secondary; sekundární struktura proteinů; Solanum lycopersicum; Crystallization; fosfáty; Binding Sites; Multienzyme Complexes